Diversity and Distribution of Marine Phytoplankton along the Coastal Areas of Gujarat, India - R., Bhagat; R., Patel; R.D., Kamboj (International Journal of Scientific Research in Biological Sciences, 2020)
Phytoplanktons are the primary producer of marine ecosystems and contribute to the primary productivity of aquatic environment. The present study was carried out at 16 different locations of Gujarat coast to ascertain the diversity & distribution of marine phytoplankton. During the study, a total 122 species of phytoplankton belonging to five different classes namely Bacillariophyceae, Cyanophyceae, Miozoaphyceae, Chlorophyceae and Charophyceae were reported from coastline of Gujarat. Of this, the highest species diversity was found at Gulf of Kachchh followed by Gulf of Khambhat > Saurashtra coast > South Gujarat coast. The maximum number of species diversity was contributed by the class Bacillariophyceae (87%) with 106 species; while the least number of species was recorded for the class Charophyceae (1 species).